Sentiment analysis of pre-service teachers’ issues and concerns during internship - Jay C. Bansale; Las Johansen B. Caluza (Indonesian Journal of Education and Pedagogy, 2026)
Student internship is a crucial component of pre-service teachers’ preparation; however, it is often accompanied by challenges that influence both their professional development and well-being. In response to these realities, this study examined the issues, concerns, and emotional responses of pre-service teachers from the Faculty of Teacher Education of Visayas State University during their internship, employing a qualitative research design integrated with sentiment analysis. Reflection narratives were collected from 208 practice teachers enrolled during the first semester of Academic Year 2025-2026.  Data were analyzed using Microsoft Excel with Copilot for thematic extraction and Orange 3 data mining software for sentiment classification. The analysis was guided by Plutchik’s Wheel of Emotions to identify dominant emotional patterns. Findings revealed seven major themes of concern: school facilities and learning environments, mentorship and supervisory relationships, academic workload, calamities and external disruptions, financial and logistical challenges, personal and emotional well-being, and self-fulfillment. Conversely, the sentiment analysis showed that while a considerable number of pre-service teachers demonstrated a neutral disposition reflecting their efforts to adapt professionally, negative emotions, especially fear, anger, and sadness, remained evident. These emotions were primarily associated with unsafe learning environments, heavy workload, unclear or inconsistent supervisory feedback, and uncertainties brought about by natural calamities. Although less dominant, positive emotions emerged through experiences of supportive mentoring that reinforce motivation. The findings underscore the importance of recognizing the emotional dimensions of pre-service teachers’ internship experiences. Addressing both structural and emotional challenges is essential for strengthening teacher education programs, enhancing mentoring practices, and fostering supportive learning environments that promote professional competence and well-being.